Safety Evaluation of Major Nuclear Facilities According to Debris Flow Occurrence Scenarios - Yeonjoong Kim; Seung-Min Park; Seon Jung Park; Heui Jung Seo (한국해양공학회지)
This study systematically analyzes the impact of sediment disasters, such as those due to debris flows, on key facilities near the Gori nuclear power plant, aiming to identify limitations in the current safety management system. Using 62 years of rainfall data from the Busan weather station, probable rainfall values for return periods of 30, 50, 100, and 200 years were analyzed. These values were applied to various debris flow scenarios to evaluate the flow characteristics and impact forces on structures. The analysis reveals that the impact forces of debris flows increase sharply for return periods of 100 years or more, indicating that existing safety protocols may not adequately account for the topographical characteristics. This study highlights the necessity of a comprehensive safety assessment framework that integrates site-specific risks such as slope and sediment dynamics. By utilizing actual rainfall data, this study provides a safety evaluation that reflects the unique geographical hazards faced by nuclear facilities. The findings offer essential data to guide future policy decisions regarding site selection, design, and operational management of nuclear facilities, ultimately improving the disaster preparedness for high-risk locations in a way that differs from existing studies.